Enhancing Economy-Class Travel: Human Ecology and Social Responsibility in Modern Airport Design - Cho, Yoonshik (Technium Social Sciences Journal, 2025)
The widening cost-to-experience disparity for international airport flyers in economy class, who represent nearly 85% of total airline flyers, is a systemic issue of amenity and comfort shortfalls. Through in-depth passenger pain point analysis, including restrictive seating arrangements, excessive wait times, restricted access to vital facilities, poor digital connections, and ineffective baggage processing, this paper discovers opportunities for impactful change in achievable operation parameters. Drawing on international case studies for 2015-2024, such as the thriving Singapore Changi Airport Terminal 4 and struggling LaGuardia Airport Terminal B, this paper delivers a tri-part solution for passenger experience optimization: redesigning physical infrastructure using modular furniture and adaptive layouts, technology solutions such as AI-driven crowding optimization and passenger flow optimization in real-time, and strategic partnership in services making premium experiences accessible. Quantitative modeling demonstrates these solutions can increase utilization of space by up to 42%, reduce costs of operation by 28%, reduce security processing time by as much as 44%, and have a major impact on passenger satisfaction metrics. The study concludes passenger experience optimization for economy class flyers is not a customer service nicety, but a strategic imperative, aligning commercial viability with corporate responsibility. With inclusive design thinking and passenger-centric strategies, airports can make environments more just and more comfortable, while remaining just as profitable, serving as a model for other public facilities with similar traffic in other regions of the globe.